Macroeconomics : a contemporary introduction : study guide - Swann, Michael J.; Lunn, John. (South Melbourne : Nelson, 1994)
The art and science of economic analysis. Some tools of economic analysis. The market system. The economic actors. Introduction to macroeconomics. Measuring economic aggregates and thecircular flow of income...
Keywords: Australia; Macroeconomics; Macroeconomics -- Study and teaching (Higher) -- Australia; Australia -- Economic conditions -- Study and teaching (Higher)